Extending the Shelf Life of Victoria Table Grapes by High Permeability and Fungicide Packaging at Room Temperature. (25th October 2012) - Xu, Wencai; Li, Dongli; Fu, Yabo; Liu, Zunzhong; Wang, Yajun; Yu, Xuemei; Shang, Wei
Abstract : Grapes are one of the most delicious fruits in the world, but normally, they only have a short shelf life at room temperature, a result of their susceptibility to body water loss and grey mould infection. In this study, we developed an active packaging film (APF), which has a sandwich structure with outer and inner layers made of zeolite‐modified low‐density polyethylene (LDPE) with fungicide additives between the two layers. The APF has high permeability for oxygen and is capable of continuously releasing low‐concentration sulfur dioxide over 48 days. The grape storage experiments showed that the shelf life of Victoria table grapes packaged in these APF‐made bags at room temperature was extended to 18 days, compared with 14 days for conventional LDPE packaging and 10 days for unpackaged grapes. At 18 days' storage in APF packaging bags, water loss, berry shatter and berry decay were less than 0.5%, 3% and 5%, respectively, whereas the total soluble solid content and firmness changed only slightly. Copyright © 2012 John Wiley & Sons, Ltd. Abstract : To extend the shelf life of Victoria grape at room temperature, an active packaging film with fungicide additives was developed. It has a high permeability for oxygen and is capable of continuously releasing low‐concentration sulfur dioxide over 48 days. Grape storage experiments showed that the shelf life of Victoria table grapes packaged in these films was extended to 18 days, compared with 14 days for conventional low‐density polyethylene packaging and 10 days for unpackaged grapes.